The making of the modern Muslim state: Islam and governance in the Middle East and North Africa - Zeghal, Malika (Princeton studies in Muslim politics, 2024)
An innovative analysis that traces the continuity of the state's custodianship of Islam as the preferred religion in the Middle East and North Africa In The Making of the Modern Muslim State, Malika Zeghal reframes the role of Islam in modern Middle East governance. Challenging other accounts that claim that Middle Eastern states turned secular in modern times, Zeghal shows instead the continuity of the state's custodianship of Islam as the preferred religion. Drawing on intellectual, political, and economic history, she traces this custodianship from early forms of constitutional governance in the nineteenth century through post-Arab Spring experiments in democracy. Zeghal argues that the intense debates around the implementation and meaning of state support for Islam led to a political cleavage between conservatives and their opponents that long predated the polarization of the twentieth century that accompanied the emergence of mass politics and Islamist movements.Examining constitutional projects, public spending, school enrollments, and curricula, Zeghal shows that although modern Muslim-majority polities have imported Western techniques of governance, the state has continued to protect and support the religion, community, and institutions of Islam. She finds that even as Middle Eastern states have expanded their nonreligious undertakings, they have dramatically increased their per capita supply of public religious provisions, especially Islamic education--further feeding the political schism between Islamists and their adversaries. Zeghal illuminates the tensions inherent in the partnerships between states and the body of Muslim scholars known as the ulama, whose normative power has endured through a variety of political regimes. Her detailed and groundbreaking analysis, which spans Tunisia, Morocco, Egypt, Turkey, Syria, and Lebanon, makes clear the deep historical roots of current political divisions over Islam in governance